Practicum-Based Learning to Improve Critical Thinking Ability and Student Learning Outcome on Cell Metabolism Material - Julita Julita; Ari Sunandar; Hanum Mukti Hanum (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2023)
Practicum in the laboratory makes students more engaged with the learning process and improves communication with the teacher. The aims of this research are to determine the effect of practicum-based learning to improve critical thinking skills and learning outcomes of students on cell metabolism material. This research includes a Pre-Experimental with One Group Pretest-Posttest Design. The sample was determined using simple random sampling techniques. Pre-tests and post-tests were done to collect data. Data analysis of learning outcomes and critical thinking skills using gain value analysis. The results of this study showed the student learning outcomes value was 24 and the value of students' critical thinking was 7. The effect size value of student learning outcomes obtained 2.3 points, which was included in the very high category and the effect size value for students' critical thinking was 1.4 points, which was included in the high category. We can conclude that practicum-based learning influences students' critical thinking and improves students' learning outcomes on metabolic matter. Keywords: cell metabolism, critical thinking, learning outcomes, practicum-based learning.